Pre-abortion counselling from women's point of view. (August 2013) - Vandamme, Joke; Wyverkens, Elia; Buysse, Ann; Vrancken, Carine; Brondeel, Ruben
Abstract Objective The value of mandatory pre-abortion counselling for women seeking abortions has been repeatedly questioned. The aim of this study was to explore the perspectives and feelings of almost 1000 women regarding pre-abortion counselling in Flanders. Methods Participating women (N = 971) – all requesting an abortion at one of the five Flemish abortion centres – were offered a questionnaire prior to the counselling session and immediately afterwards. Both questionnaires measured their emotional and cognitive state as well as aspects of the content and the perceived value of the counselling session. Results Prior to the counselling, women are hesitant regarding the value of the sessions, feel distressed, yet decisive about their abortion. After the counselling session, women assign an increased value to the counselling, are very satisfied, and experience less distress and greater decisiveness. During counselling the abortion procedure (89%), the use of contraceptives (83%) and the individual decision-making process (81%) are nearly always addressed. The sessions are tailored to each woman and to the needs they expressed with regard to the content of the counselling. Conclusions Pre-abortion counselling in Flanders is standardised as well as personalised. The women in this study positively valued it.